Phenotypic Variations in Calligonum comosumL`Her (Polygonaceae) Grown in Al-Nefud Desert in Saudi Arabia - Taia, W. K.; Moussa, S. A. I. (Journal of Scientific Research, 2011)
Vegetative community structures and phenotypic variations within Calligonum comosum L`Her individuals grown in two different locations in Al-Nefud desert in Saudi Arabia; Nefud Al-Shakika and Al-Dahnaa, have been studied. Eleven species have been recorded in both areas; five of them were present in both locations. Ephedra elata and Convolvulus lanatus were recorded in Nefud Al-Shakika only. While Heliotropium bacciferum, Cleome arabica, Dodonaea viscosa and Erodium gleurocophyllum were found in Al-Dahnaa only. The importance values of the species recorded have been calculated and cluster analyses of the studied quadrates have been made using TWINSPAN method. Vegetative morphological characters showed great variations within C. comosum collected from the two locations. Floral morphological characters are more stable, except the fruit colour and hair which was different in the C. comosum plants grown in the two locations. Epidermal stem secretions as well as mineral contents varied in response to change in locations. ANOVA test have been carried out to evaluate the differences between the two areas. The variations in these characters are discussed according to the difference in climates, soil characters and water availability. Keywords: Phenotypic variation; Vegetative morphology; Fruit morphology; Pollen grains; Mineral contents; Al-Nefud- Al-Dahnaa. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i2.7010 J. Sci. Res. 3 (2), 421-435 (2011)